COSTUMER SATISFACTION ANALYSIS OF RICE BRAN COFFEE PRODUCTS - Winda Amilia; Clara Septaria Melinda; Andrew Setiawan Rusdianto; Nita Kuswardhani; Miftahul Choiron (UPT Penerbitan Universitas Jember, 2022)
Legendaris Koka is a company that provides various kinds of coffee innovations, one of them is ricebran coffee is located on Jl. Letjen. Panjaitan No. 22 Jember Regency. Rice bran coffee is a coffee blended with rice bran after roasting process with the aim of creating a distinctive taste and aroma from the combination of coffee and rice bran. The purpose of this research is to determine the attributes of importance and the value of suitability of importance on performance and consumer satisfaction